Target Tracking in Wireless Sensor Networks - Ahmad, Tauseef (2021)
A Wireless Sensor Network (WSN) consists of a group of tiny devices called sensors that communicate through wireless links. Sensors are used to collect data about some parameters and send the collected data for further processing to a designated station. The designated station is often called command and control center (CCC), fusion center (FC), or sink. Sensors forward the collected data to their leaders or cluster heads, which in turn send it to the centralized station. There are many applications of a WSN such as environmental monitoring, raising alarms for fires in forests and multi-storied buildings, monitoring habitats of wild animals, monitoring children in a kindergarten, support system in play grounds, monitoring indoor patients in a hospital, precision agriculture, detection of infiltration along international boundaries, tracking an object or a target, etc.